2020
DOI: 10.1038/s41598-020-64331-7
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Distribution Width is Associated with Future Incidence of Abdominal Aortic Aneurysm in a Population-Based Cohort Study

Abstract: Red cell distribution width (RDW) has been suggested to have a predictive potential for several cardiovascular diseases, but its association with abdominal aortic aneurysm (AAA) is unknown. We examined whether RDW is associated with the risk of AAA among 27,260 individuals from the population-based Malmö Diet and Cancer Study cohort. Data of baseline characteristics were collected during 1991-1996. Cox regression was used to estimate hazard ratios (HR) with 95% confidence intervals (CI) for AAA across quartile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…LabWAS results (Supplemental Figure 12, Supplemental Table 9) indicate that changes in erythrocytes distribution width is associated with aortic aneurysms. Erythrocytes wide distribution association with aortic aneurysms is reported 43 and based in our findings may be a good clinical laboratory test to detect aortic aneurysm. The clinical cardiac parameters QRS duration and ST segment ware associated with aortic aneurysm in our analysis.…”
Section: Discussionsupporting
confidence: 68%
“…LabWAS results (Supplemental Figure 12, Supplemental Table 9) indicate that changes in erythrocytes distribution width is associated with aortic aneurysms. Erythrocytes wide distribution association with aortic aneurysms is reported 43 and based in our findings may be a good clinical laboratory test to detect aortic aneurysm. The clinical cardiac parameters QRS duration and ST segment ware associated with aortic aneurysm in our analysis.…”
Section: Discussionsupporting
confidence: 68%
“…Finally, several limitations should be stated and might be improved in future studies if possible. The previous study indicated that RDW was a stronger risk factor for AAA in smokers than in nonsmokers, [22] and we were unclear whether the association between RDW and in-hospital death can be mediated by smoking status. Our study did not include the smoking status in the final analysis, as there are too many missing values about the smoking history.…”
Section: Discussionmentioning
confidence: 91%
“…Also, our previous studies reported RDW was associated with mortality and abdominal aortic aneurysm after multiple adjustments of routine laboratory parameters (i.e., WBC, etc.) ( 5 , 47 ). Hence, other routine laboratory parameters do not seem to fully explain the relationships between RDW and mortality or cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%